2023
DOI: 10.33003/fjs-2022-0606-1113
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Sites Characteristics and Mosquito Abundance in Some Selected Locations Within Kaduna Metropolis

Abstract: Natural or artificial collection of water serves as an optimum habitat that supports mosquito’s breeding, while savannah, grasslands or shady low woodlands supports their resting activities, swarming and mating. Samples were collected from breeding sites within some selected locations from January to June. Five hundred and thirty two mosquito larvae belonging to 3 genera Culex, Anopheles and Aedes were collected and seven species of mosquitoes were identified comprising; Culex quinquefasciatus 102 (19.17%), Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Similar findings have been reported by Abril et al, (2010) on the effect of temperature on the development and survival of the Argentine ant, Linepithema humile. Findings from this study on insect carrion abundance corroborates findings by Oguche et al, (2022) that showed correlation between environmental variables and mosquito abundance in some selected locations within Kaduna metropolis.…”
Section: Variations In Environmental Variables At the Field Sitesupporting
confidence: 89%
“…Similar findings have been reported by Abril et al, (2010) on the effect of temperature on the development and survival of the Argentine ant, Linepithema humile. Findings from this study on insect carrion abundance corroborates findings by Oguche et al, (2022) that showed correlation between environmental variables and mosquito abundance in some selected locations within Kaduna metropolis.…”
Section: Variations In Environmental Variables At the Field Sitesupporting
confidence: 89%
“…Dissolved oxygen, biological oxygen demand, pH, and nutrients evaluated in this study were positively correlated and negatively correlated with turbidity. The presence of of nitrates, nitrites, ammonia, and phosphates can be attributed to the use of fertilisers containing ammonium and phosphorus in the farms since most of the sites were adjacent to the farms, while turbidity is associated with silt, mud, algae, and plant pieces [51, 73, 75, 76]. The high level of nutrients has been reported to promote excessive growth of water plants and microorganisms in the water bodies which reduces turbidity of the water making it more suitable for the proliferation of mosquitoes [77, 78].…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved oxygen, biological oxygen demand, pH, and nutrients evaluated in this study were positively correlated and negatively correlated with turbidity. The presence of of nitrates, nitrites, ammonia, and phosphates can be attributed to the use of fertilisers containing ammonium and phosphorus in the farms since most of the sites were adjacent to the farms, while turbidity is associated with silt, mud, algae, and plant pieces [51,73,75,76].…”
Section: Physicochemical Parameters Of the Sitesmentioning
confidence: 99%